Monatomic tin catalyst for acetylene hydrochlorination reaction as well as preparation method and application of monatomic tin catalyst
By using chitosan and glacial acetic acid to prepare nitrogen-anchored single-atom tin catalysts in the acetylene hydrochlorination reaction, the problems of easy loss of active components of tin-based catalysts are solved, and efficient catalytic performance and long-term Time stability, suitable for industrial applications.
Patent Information
- Application Number
- CN202411450291.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-03
AI Technical Summary
The active components of tin-based catalysts are prone to be lost in the acetylene hydrochlorination reaction, have low catalytic activity and poor catalytic stability.
Using chitosan, glacial acetic acid and stannous chloride as raw materials, a nitrogen-anchored single-atom tin catalyst was prepared by hydrothermal method, and the nitrogen doping steps were avoided by using chitosan's high nitrogen content, through impregnation, calcination and The process of pickling and other processes obtains a catalyst with high activity and high stability.
Achieve higher acetylene conversion rate (>98%) and longer time stability (>150 hours) at lower reaction temperatures (180°C), reducing catalyst preparation costs and energy consumption, and improving the industrial application potential of catalysts .
Smart Images

Figure CN119236994A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new materials, and specifically relates to a preparation method of a tin single-atom catalyst and an application of the catalyst in the reaction of preparing vinyl chloride by acetylene hydrochlorination. Background Art
[0002] Polyvinyl chloride (PVC) is an engineering plastic widely used in daily life. Ground film, water pipes and the insulating sheath of wires are all made of polyvinyl chloride as raw materials, so the market demand is huge. The current production processes of its monomer vinyl chloride (VCM) mainly include the following four methods: ethane method, ethylene method, acetylene method and "Jiang Zhong" method. Due to the advantage of my country's rich coal resources, the acetylene method for preparing vinyl chloride is the main production process for producing VCM in my country. At present, the acetylene method for preparing VCM in industry uses HgCl 2 / AC catalysts, this type of catalyst has the disadvantages of being volatile and unfriendly to the human body and the environment; at the same time, due to the dual constraints of the Minamata Convention and the "dual carbon goals", the development of new non-mercury-based catalysts has become a research hotspot in the preparation of VCM by acetylene.
[0003] At present, the catalysts used to prepare vinyl chloride monomer by the acetylene method mainly include metal-based catalysts and non-metal-based catalysts, and metal-based catalysts are further divided into precious metal-based catalysts and non-precious metal-based catalysts. At present, the catalysts that are studied more are mainly gold, platinum, copper and carbon catalysts. Li Wei's research group at Nankai University modified gold nanoparticles (Au / AC) loaded on activated carbon (AC) with two ligands, N-chlorosuccinimide and N-methylsuccinimide, and found that when the gold loading was 0.1wt.%, at a reaction temperature of 180°C and an acetylene volume space velocity of 160h -1 Under the reaction conditions, the conversion rates of acetylene can reach 98% and 88% respectively, which are better than Au / AC catalysts (ChemCatChem, 2022, e202200785). The patent with publication number: CN117299213A discloses a precious metal platinum-based catalyst for acetylene hydrochlorination reaction and its preparation method and application. The catalyst includes activated carbon, platinum species, and auxiliary agents containing N, O, S, P, etc., mainly including one of phenylphosphonyl dichloride, nitrosobenzene, methylphenyl sulfoxide, acetophenone and p-pentylacetophenone. The platinum-based catalyst prepared by impregnation can effectively improve the catalytic activity and stability. Although the precious metal-based catalyst exhibits higher catalytic performance, its active components are expensive, difficult to recover, and the catalyst is easily deactivated, which is not conducive to industrial application. Zhang Jinli's research group at Tianjin University used methyl diphenylphosphine oxide as a copper ligand to prepare 15% Cu 8 MDPO 1 / AC catalyst and at 180℃, 180h -1(C 2 H 2 ) under the condition of acetylene conversion rate is stable at 97%, and the industrial sideline test after 3414 hours of continuous reaction found that the acetylene conversion rate of the catalyst is still maintained at more than 85%, showing excellent catalytic activity and stability (ACS Sustainable Chemistry Engineering, 2023, 11, 5, 1666-1677), but due to its ligand synthesis steps are cumbersome and the price is relatively high, it is difficult to reduce the preparation cost of the catalyst. The patent with publication number: CN116510763A discloses a metal-free catalyst for acetylene hydrochlorination reaction and its preparation method and application. The catalyst reduces the carbon dioxide in the mixed gas through magnesium thermal reaction in a tubular furnace, and at the same time, it is doped with nitrogen atoms and coated on a silicon oxide carrier to form a carbon-nitrogen coated composite carbon-based catalyst. The catalyst prepared by this method has a reaction temperature of 200°C and an acetylene volume space velocity of 30h -1 Under the conditions of , the conversion rate of acetylene is higher than 80%, but compared with metal-based catalysts, the reaction conditions of non-metal-based catalysts are more stringent, thus increasing the investment cost of the equipment.
[0004] The preparation of cheap, highly active and stable acetylene hydrochlorination catalysts is the current research focus.
[0005] Compared with the above catalysts, tin, as one of the non-precious metals, has the advantages of abundant reserves and low price, and also shows good catalytic performance in the acetylene hydrochlorination reaction. Xue Jianwei's research group at Taiyuan University of Technology prepared Sn-MOFs / AC catalyst supported on activated carbon by using the unique structure and physicochemical properties of metal organic frameworks (MOFs). The catalyst can be heated to 200℃ for 30h. -1 (C 2 H 2 ) under the conditions of 93.5%, but after 40 hours of continuous reaction, the conversion rate of acetylene dropped to 52.6% (Chemistry Select, 2019, 4, 9403-9409). Dai Bin's research group used tin tetrachloride and activated carbon to prepare SnO by hydrothermal method. x / AC catalyst showed good catalytic performance. Under the reaction conditions of 180℃, 90h -1 (C 2 H 2 ) under the condition of 5% acetylene conversion, they found that at higher reaction temperatures, the main reason for catalyst deactivation was that tin oxide was converted into tin chloride and vaporized, resulting in the loss of active components (NanoResearch, 2023, 16, 6577-6583). Summary of the invention
[0006] The invention aims to solve the problems of easy loss of active components of tin-based catalysts, low catalytic activity and poor catalytic stability in acetylene hydrochlorination reaction, and provides a preparation method for preparing a nitrogen atom-anchored single-atom tin catalyst using chitosan, glacial acetic acid and stannous chloride as raw materials. The catalyst is applied to acetylene hydrochlorination reaction and has the advantages of simple preparation method, no need for nitrogen doping step, cheap and easy to obtain raw materials, high catalytic activity and good stability. It is also the first time that a tin single-atom catalyst is applied to acetylene hydrochlorination reaction.
[0007] In view of the shortcomings of tin nanoparticle-based catalysts, such as easy loss of active components and poor catalytic stability, regulating the valence state and existence form of tin nanoparticles is the main method to solve this problem.
[0008] Chitosan is used as a carbon source because it contains a large amount of nitrogen atoms, and no nitrogen doping is required, thereby saving raw materials and energy consumption in the doping process. The innovation of the present invention is to use chitosan as a carbon source, prepare activated carbon with high nitrogen content by a simple hydrothermal method, and prepare a highly active and stable single-atom tin acetylene hydrochlorination catalyst by impregnation, calcination, acid washing and other processes.
[0009] Technical solution of the present invention
[0010] A method for preparing a single-atom tin catalyst with high catalytic performance and stability for acetylene hydrochlorination reaction, the specific method is as follows:
[0011] (1) using a carbon source with a high nitrogen content such as chitosan, glacial acetic acid and deionized water, stirring and mixing to form a gel;
[0012] (2) preparing the obtained gel by a hydrothermal method to obtain a carbon precursor with a high nitrogen content, and then washing, drying and grinding to obtain a carbon support;
[0013] (3) dissolving the carbon support and stannous chloride in water, stirring and mixing, and stirring and evaporating the resulting solution to dryness to obtain a catalyst precursor A;
[0014] (4) placing the obtained catalyst precursor A into a tubular furnace and performing heat treatment according to a programmed temperature increase to obtain a catalyst precursor B;
[0015] (5) The catalyst precursor B is washed with an acidic solution, then washed with deionized water until it is neutral, and then dried to obtain a nitrogen-anchored single-atom tin catalyst.
[0016] Furthermore, in some implementation methods, the mass ratio of glacial acetic acid to chitosan in step (1) is 0.5 wt.% to 10 wt.%.
[0017] In some implementation methods, the hydrothermal reaction temperature in step (2) is 150-200°C, the hydrothermal reaction time is 6-24h, the carbon carrier drying temperature is 60-120°C, and the drying time is 12-24h. The preferred hydrothermal temperature is 170-190°C, and the hydrothermal time is 8-16h; the preferred carbon carrier drying temperature is 80-100°C, and the drying time is 18-24h.
[0018] In some implementation methods, the mass ratio of the carbon support to stannous chloride in step (3) is 1:0.25-2, preferably 1:0.5-1.5; the mixture is stirred and evaporated for 6-24 hours, preferably 8-12 hours; and the temperature for stirring and evaporating is 60-120°C, preferably 80-100°C.
[0019] In some implementation methods, the procedure of the heat treatment in step (4) is that the initial temperature is 30°C, the heating rate is 1-10°C / min, the temperature is increased to 400-800°C, and the temperature is maintained for 1-6h, preferably the heating rate is 3-5°C / min, the temperature is preferably 500-700°C, and the heat treatment time is preferably 2-4h. The heat treatment process needs to be carried out in a certain atmosphere, the atmosphere is an inert gas, specifically one or a mixture of nitrogen, argon, helium or ammonia, preferably nitrogen or argon; the flow rate of the atmosphere is 10-100mL / min, and the preferred atmosphere flow rate is 20-50mL / min.
[0020] In some implementation methods, the acidic solution used for pickling in step (5) is one or more of hydrochloric acid, nitric acid, sulfuric acid or aqua regia, the concentration of the acidic solution is 1 to 6 mol / L, the pickling time is 8 to 24 hours, and the pickling temperature is 20 to 80° C. The preferred acidic solution is hydrochloric acid or aqua regia, the preferred acidic solution concentration is 2 to 4 mol / L, the preferred pickling time is 10 to 16 hours, and the preferred pickling temperature is 30 to 60° C.
[0021] On the other hand, the present invention also provides the use of the above-mentioned single-atom tin catalyst in the preparation of vinyl chloride by acetylene hydrochlorination.
[0022] In some implementation methods, the temperature of the acetylene hydrochlorination reaction is 150-220°C, and the acetylene reaction space velocity is 30-360h -1 The activation time of hydrogen chloride is 15 to 90 minutes, and the molar ratio of hydrogen chloride to acetylene is 1:1 to 1.5:1.
[0023] Advantages and beneficial effects of the present invention:
[0024] (1) The single-atom tin catalyst carrier of the present invention adopts the biomass raw material chitosan, which has the advantages of being green, environmentally friendly, and sustainable, and has a simple preparation process and does not require a large amount of energy for calcination.
[0025] (2) Compared with other tin-based catalysts, the single-atom tin catalyst of the present invention has a lower reaction temperature (T = 180 ° C) and a higher acetylene space velocity (GHSV = 90h -1 ) showed better catalytic performance (acetylene conversion rate>98%) and catalytic stability (catalytic stability>150h), providing a reference for its future industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a spherical aberration corrected transmission electron micrograph of the single-atom tin catalyst of Example 2 of the present invention.
[0027] Figure 2 This is a stability test curve of the acetylene hydrochlorination reaction of the single-atom tin catalyst of Example 2 of the present invention and the supported tin catalyst of Comparative Example 1. DETAILED DESCRIPTION
[0028] The raw materials used in the present invention are all common commercial products, and their sources are not specifically limited. The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments, so that those skilled in the art can implement it according to the description.
[0029] A method for preparing a single-atom tin catalyst with high catalytic performance and stability for acetylene hydrochlorination reaction, the specific method is as follows:
[0030] (1) Dissolve chitosan in deionized water, add glacial acetic acid, and stir until it becomes a paste, wherein the mass ratio of chitosan to glacial acetic acid is 0.5wt% to 10wt%.
[0031] (2) The obtained paste is placed in a stainless steel autoclave containing a polytetrafluoroethylene liner for reaction, and then filtered, washed with deionized water, and dried to obtain a carbon support.
[0032] In some implementation methods, the hydrothermal reaction temperature is 150-200° C., the hydrothermal reaction time is 6-24 h, the drying temperature of the carbon support is 60-120° C., and the drying time is 12-24 h.
[0033] (3) The obtained carbon support is mixed with stannous chloride solutions of different mass ratios, and the mixture is evaporated to dryness at 60-120° C. to obtain a catalyst precursor A.
[0034] In some implementation methods, the mass ratio of the carbon support to stannous chloride is 1:0.25-2, and the mixture is stirred for 6-24 hours.
[0035] (4) The obtained solid catalyst precursor A is placed in a tubular furnace and calcined in an inert atmosphere to obtain a catalyst precursor B.
[0036] In some implementation methods, the inert gas is nitrogen, argon, helium or ammonia, the calcination temperature is 400-800° C., and the calcination time is 1-6 hours.
[0037] (5) The calcined solid catalyst precursor B is acid-washed, filtered, washed with deionized water, and dried to obtain a single-atom tin catalyst.
[0038] In some implementation methods, the acid solution used for pickling is hydrochloric acid, nitric acid, sulfuric acid or aqua regia, the concentration of the acid solution is 1-6 mol / L, the pickling time is 8-24 h, and the pickling temperature is 20-80°C.
[0039] Example 1
[0040] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.03 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor with a polytetrafluoroethylene liner, react at 150 ° C for 6 hours, and after cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 60 ° C for 24 hours to obtain a carbon carrier.
[0041] The dried carbon carrier was ground into powder, and 3 g of carbon carrier powder and 0.75 g (mass ratio of 1:0.25) of dihydrate stannous chloride solid were weighed and dissolved in 50 mL of deionized water, stirred at 60 ° C for 6 h, and the catalyst was evaporated at 60 ° C with stirring to obtain catalyst precursor A. The dried catalyst precursor A was placed in a tube furnace, and heated to 600 ° C at a rate of 1 ° C / min in a helium atmosphere of 10 mL / min, and kept warm for 1 h. Naturally cooled to room temperature, the obtained solid catalyst precursor B was placed in 100 mL of 1 mol / L nitric acid solution, washed at 20 ° C for 24 h, and then the solid was filtered and washed to neutral, and dried at 80 ° C for 12 h to obtain single atomic tin catalyst A.
[0042] Take 2 mL of catalyst A and load it into a fixed bed reactor. Add nitrogen and heat to 180°C. Add hydrogen chloride to activate for 30 min, then add acetylene. At 180°C and acetylene volume space velocity of 90 h -1 The reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1.15:1, and the catalytic performance was shown in Table 1.
[0043] Example 2
[0044] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.53 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor containing a polytetrafluoroethylene liner. React at 180°C for 12 hours. After cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 80°C for 24 hours to obtain a carbon carrier.
[0045] The dried carbon carrier was ground into powder, and 3g of carbon carrier powder and 3g (mass ratio of 1:1) of dihydrated stannous chloride solid were weighed and dissolved in 50mL of deionized water, stirred at 60°C for 12h, and the catalyst was evaporated with stirring at 80°C to obtain catalyst precursor A. The dried catalyst precursor A was placed in a tube furnace, and the temperature was increased to 600°C at a heating rate of 5°C / min under a nitrogen atmosphere of 50mL / min, and kept warm for 2h. Naturally cooled to room temperature, the obtained solid catalyst precursor B was placed in 100mL of 2mol / L hydrochloric acid solution, washed at 60°C for 12h, then the solid was filtered and washed to neutrality, and dried at 80°C for 12h to obtain single atomic tin catalyst B.
[0046] Take 2 mL of catalyst B and load it into a fixed bed reactor. Add nitrogen and heat to 180°C. Add hydrogen chloride to activate for 30 min, then add acetylene. At 180°C and acetylene volume space velocity of 90 h -1 The reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1.15:1, and the catalytic performance was shown in Table 1.
[0047] Example 3
[0048] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.6 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor with a polytetrafluoroethylene liner. React at 200 ° C for 24 hours. After cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 120 ° C for 12 hours to obtain a carbon carrier.
[0049] The dried carbon carrier was ground into powder, and 3g of carbon carrier powder and 6g (mass ratio of 1:2) of dihydrate stannous chloride solid were weighed and dissolved in 50mL of deionized water, stirred at 60°C for 24h, and stirred and evaporated the catalyst at 120°C to obtain catalyst precursor A. The dried catalyst precursor A was placed in a tube furnace, and heated to 600°C at a rate of 10°C / min under an argon atmosphere of 100mL / min, and kept warm for 6h. Naturally cooled to room temperature, the obtained solid catalyst precursor B was placed in 100mL of 6mol / L nitric acid solution, washed at 80°C reflux for 8h, then the solid was filtered and washed to neutrality, and dried at 80°C for 12h to obtain single atomic tin catalyst C.
[0050] Take 2 mL of catalyst C, load it into a fixed bed reactor, introduce nitrogen and heat it to 180°C, introduce hydrogen chloride to activate it for 30 min, and then introduce acetylene. At 180°C and acetylene volume space velocity of 90 h -1 The reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1.15:1, and the catalytic performance was shown in Table 1.
[0051] Example 4
[0052] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.53 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor containing a polytetrafluoroethylene liner. React at 180°C for 12 hours. After cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 80°C for 24 hours to obtain a carbon carrier.
[0053] The dried carbon carrier was ground into powder, and 3g of carbon carrier powder and 3g (mass ratio of 1:1) of dihydrated stannous chloride solid were weighed and dissolved in 50mL of deionized water, stirred at 60°C for 12h, and the catalyst was evaporated with stirring at 80°C to obtain catalyst precursor A. The dried catalyst precursor A was placed in a tube furnace, and the temperature was increased to 400°C at a heating rate of 5°C / min under a nitrogen atmosphere of 50mL / min, and kept warm for 2h. Naturally cooled to room temperature, the obtained solid catalyst precursor B was placed in 100mL of 2mol / L hydrochloric acid solution, washed at 60°C for 12h, then the solid was filtered and washed to neutrality, and dried at 80°C for 12h to obtain single-atom tin catalyst D.
[0054] Take 2 mL of catalyst D, load it into a fixed bed reactor, introduce nitrogen and heat it to 150°C, introduce hydrogen chloride to activate it for 30 min, and then introduce acetylene. At 150°C and acetylene volume space velocity of 30 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1:1, and the catalytic performance was shown in Table 1.
[0055] Example 5
[0056] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.53 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor containing a polytetrafluoroethylene liner. React at 180°C for 12 hours. After cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 80°C for 24 hours to obtain a carbon carrier.
[0057] The dried carbon carrier was ground into powder, and 3g of carbon carrier powder and 3g (mass ratio of 1:1) of dihydrated stannous chloride solid were weighed and dissolved in 50mL of deionized water, stirred at 60°C for 12h, and the catalyst was evaporated with stirring at 80°C to obtain catalyst precursor A. The dried catalyst precursor A was placed in a tube furnace, and the temperature was increased to 800°C at a heating rate of 5°C / min under a nitrogen atmosphere of 50mL / min, and kept warm for 2h. Naturally cooled to room temperature, the obtained solid catalyst precursor B was placed in 100mL of 2mol / L hydrochloric acid solution, washed at 60°C for 12h, then the solid was filtered and washed to neutrality, and dried at 80°C for 12h to obtain single atomic tin catalyst E.
[0058] Take 2 mL of catalyst E, load it into a fixed bed reactor, introduce nitrogen, raise the temperature to 220°C, introduce hydrogen chloride to activate for 30 min, and then introduce acetylene. At 220°C and acetylene volume space velocity of 360 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1.5:1, and the catalytic performance was shown in Table 1.
[0059] Comparative Example 1
[0060] Weigh 6 g of chitosan and dissolve it in 50 mL of deionized water, add 0.53 g of glacial acetic acid, stir until it becomes a paste, and put it into a reactor containing a polytetrafluoroethylene liner. React at 180°C for 12 hours. After cooling to room temperature, filter the obtained solid and wash it with a large amount of deionized water until it is neutral, and dry it in an oven at 80°C for 24 hours to obtain a carbon carrier.
[0061] The dried carbon carrier was ground into powder, and 3 g of carbon carrier powder and 0.23 g of stannous chloride dihydrate solid were weighed to prepare a catalyst with the same tin content as in Example 2, and dissolved in 50 mL of deionized water, stirred at 60 ° C for 12 h, and stirred and evaporated the catalyst at 80 ° C to obtain a supported catalyst precursor. The dried catalyst was placed in a tubular furnace, heated to 600 ° C at a heating rate of 5 ° C / min under a nitrogen atmosphere of 50 mL / min, and kept warm for 2 h. Naturally cooled to room temperature to obtain a supported tin catalyst F.
[0062] Take 2 mL of catalyst F, load it into a fixed bed reactor, introduce nitrogen, raise the temperature to 180°C, introduce hydrogen chloride to activate for 30 min, and then introduce acetylene. At 180°C and acetylene volume space velocity of 90 h -1 The reaction was carried out under the condition that the volume ratio of hydrogen chloride to acetylene was 1.15:1, and the catalytic performance was shown in Table 1.
[0063] To prove that the catalyst of the present invention exists in the form of single atoms, Figure 1 Aberration-corrected transmission electron microscopy image of catalyst B is shown, with the bright spots being single tin atoms.
[0064] Table 1 Catalytic performance of acetylene hydrochlorination reaction with different catalysts
[0065]
[0066] The catalyst stability test was carried out using catalyst B and catalyst F at a reaction temperature of 180°C and an acetylene volume space velocity of 90 h -1 , the reaction was carried out under the condition that the volume ratio of vinyl chloride to acetylene was 1.15:1. After continuous reaction for 150 hours, the activity of the catalyst in Example 2 decreased by about 23.08% to 76%; after reaction for 20 hours, the catalytic activity of the catalyst in Comparative Example 1 decreased by about 51.27% to 38.74%. The results are as follows Figure 2 shown.
[0067] From the catalytic test results of the above catalyst for acetylene hydrochlorination reaction, it can be seen that compared with the supported tin nanoparticle catalyst, the catalytic activity and catalytic stability of the single-atom tin catalyst are greatly improved. Compared with the tin-based catalysts in other documents, the catalyst of the present invention uses single-atom tin as the catalyst active component for the first time, and has obvious advantages in catalytic performance and catalytic stability.
[0068] The experimental process and details described in the examples are preferred preparation and experimental conditions of the present invention and do not limit the present invention. Modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should all be included in the protection scope of the present invention.
Claims
1. A method for preparing a single-atom tin catalyst for acetylene hydrochlorination, characterized in that: (1) using a carbon source with a high nitrogen content such as chitosan, glacial acetic acid and deionized water, stirring and mixing to form a gel; (2) preparing the obtained gel by a hydrothermal method to obtain a carbon precursor with a high nitrogen content, and then washing, drying and grinding to obtain a carbon support; (3) dissolving the carbon support and stannous chloride in water, stirring and mixing, and stirring and evaporating the resulting solution to dryness to obtain a catalyst precursor A; (4) placing the obtained catalyst precursor A into a tubular furnace and performing heat treatment according to a programmed temperature increase to obtain a catalyst precursor B; (5) The catalyst precursor B is washed with an acidic solution, then washed with deionized water until it is neutral, and then dried to obtain a nitrogen-anchored single-atom tin catalyst.
2. The preparation method according to claim 1, characterized in that: The mass ratio of glacial acetic acid to chitosan in step (1) is 0.5wt.% to 10wt.%.
3. The preparation method according to claim 1, characterized in that: The hydrothermal temperature in step (2) is 150-200°C, and the hydrothermal time is 6-24h; the carbon carrier drying temperature is 60-120°C, and the drying time is 12-24h; the preferred hydrothermal temperature is 170-190°C, and the preferred hydrothermal time is 8-16h; the preferred carbon carrier drying temperature is 80-100°C, and the preferred drying time is 18-24h.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the carbon support to stannous chloride in step (3) is 1:0.25-2, preferably 1:0.5-1.5; the stirring and evaporating time of the mixed solution is 6-24 hours, preferably 8-12 hours; the stirring and evaporating temperature is 60-120°C, preferably 80-100°C.
5. The preparation method according to claim 1, characterized in that: The procedure of the heat treatment in step (4) is as follows: the initial temperature is 30°C, the heating rate is 1-10°C / min, the temperature is increased to 400-800°C, and the temperature is maintained for 1-6h; the preferred heating rate is 3-5°C / min, the preferred temperature is 500-700°C, and the preferred heat treatment time is 2-4h.
6. The preparation method according to claim 5, characterized in that: The heat treatment process needs to be carried out in a certain atmosphere, which is one of nitrogen, argon, helium or ammonia or a mixture of two of them, wherein the preferred atmosphere is nitrogen or argon; the flow rate of the atmosphere is 10 to 100 mL / min, and the preferred atmosphere flow rate is 20 to 50 mL / min.
7. The preparation method according to claim 1, characterized in that: The acidic solution used for pickling in step (5) is one or more of hydrochloric acid, nitric acid, sulfuric acid or aqua regia, the concentration of the acidic solution is 1 to 6 mol / L, the pickling time is 8 to 24 h, and the pickling temperature is 20 to 80 ° C; the preferred acidic solution is hydrochloric acid or aqua regia, the preferred acidic solution concentration is 2 to 4 mol / L, the preferred pickling time is 10 to 16 h, and the preferred pickling temperature is 30 to 60 ° C.
8. A single-atom tin catalyst prepared by the method according to any one of claims 1 to 7.
9. The use of the single-atom tin catalyst according to claim 8, characterized in that: The catalyst is used for the reaction of acetylene hydrochlorination to produce vinyl chloride.
10. The use according to claim 9, characterized in that: The application temperature of the catalyst is 150-220°C, and the acetylene reaction space velocity is 30-360h -1 , the molar ratio of hydrogen chloride to acetylene is 1:1 to 1.5:1.
Citation Information
Cited By
Nitrogen / sulfur self-doped hierarchical porous carbon catalyst as well as preparation method and application thereof
CN120790202A